A study on the occupational health concerns and safety of library employees of the University of the Philippines Diliman Library System - Cadiz, Nino Mar Angelo R.; Ramos, Marian S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
This is a descriptive study of common occupational health and safety illnesses and diseases among the 128 library staff of University of the Philippines Diliman. It aims to investigate the various occupational health and safety illnesses and diseases among the library staff by tasks. It further identifies the causes of such illnesses and diseases as well as the preventive measures that were employed by the library administration and personnel.
Findings show that eyestrain emerged as the leading occupational health and safety illness and disease concern of the library employees which is attributed to the overuse of personal computers needed to perform efficiently the library tasks. Other leading health concerns include backache and awkward posture, muscle pains, headache and dizziness and Carpal Tunnel Syndrome. Warts are the least health concern of library employees. Also, majority of the employees do not feel safe and healthy in their workplaces mainly due to dust, poor ventilation and unsafe structure. To be safe and healthy, library staff prioritizes cleanliness and orderliness, health management and hygiene. On the other hand, library administrators conduct seminars, trainings and cleanliness drives to address the health concerns of library workers. Library staff do have health concerns and this study further concludes that the UP Diliman Library System needs to prioritize further the health and safety of their employees. Employees must properly acknowledge that they are exposed to several health hazards during work and must be able to work on it by being able to take care of themselves better whether inside or outside their respective workplaces.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman) -- Libraries; Library employees -- Health and hygiene -- Philippines -- Quezon City; Industrial hygiene -- Philippines -- Quezon City; Industrial safety -- Philippines -- Quezon City